A novel synthesis of 6′′‐[18F]‐fluoromaltotriose as a PET tracer for imaging bacterial infection. (30th March 2018) - Namavari, Mohammad; Gowrishankar, Gayatri; Srinivasan, Ananth; Gambhir, Sanjiv S.; Haywood, Thomas; Beinat, Corinne
Abstract : The aim of this study was to develop a positron emission tomography (PET) tracer to visualize and monitor therapeutic response to bacterial infections. In our continued efforts to find maltose based PET tracers that can image bacterial infections, we have designed and prepared 6′′‐[ 18 F]fluoromaltotriose as a second generation PET imaging tracer targeting the maltodextrin transporter of bacteria. We have developed methods to synthesize 6′′‐deoxy‐6′′‐[ 18 F]fluoro‐α‐D‐glucopyranosyl‐(1‐4)‐O‐α‐D‐glucopyranosyl‐(1‐4)‐O‐D‐glucopyranose (6′′‐[ 18 F]‐fluoromaltotriose) as a bacterial infection PET imaging agent. 6′′‐[ 18 F]fluoromaltotriose was prepared from precursor, 2′′, 3′′, 4′′‐tri‐O‐acetyl‐6′′‐O‐nosyl‐α‐D‐glucopyranosyl‐(1‐4)‐O‐2′, 3′, 6′‐tri‐O‐acetyl‐α‐D‐glucopyranosyl‐(1‐4)‐1, 2, 3, 6‐tetra‐O‐acetyl‐D‐glucopyranose (per‐O‐acetyl‐6′′‐O‐nosyl‐maltotriose4 ). This method utilizes the reaction between precursor4 and anhydrous [ 18 F]KF/Kryptofix 2.2.2 in dimethylformamide (DMF) at 85°C for 10 minutes to yield per‐O‐acetyl‐6′′‐deoxy‐6‐′′ [ 18 F]‐fluoromaltotriose (7) . Successive acidic and basic hydrolysis of the acetyl protecting groups in7 produced 6′′‐[ 18 F]fluoromaltotriose (8 ). Also, cold 6′′‐ [ 19 F]fluoromaltotriose was prepared from per‐O‐acetyl‐6′′‐hydroxymaltotriose via a diethylaminosulfur trifluoride reaction followed by a basic hydrolysis. A successful synthesis of 6′′‐[ 18 F]‐fluoromaltotriose has been accomplished in 8 ± 1.2% radiochemical yield (decay corrected). Total synthesis time was 120 minutes. Serum stability of 6′′‐[ 18 F]fluoromaltotriose at 37°C indicated that 6′′‐[ 18 F]‐fluoromaltotriose remained intact up to 2 hours. In conclusion, we have successfully synthesized 6′′‐[ 18 F]‐fluoromaltotriose via direct fluorination of an appropriate precursor of a protected maltotriose. Abstract : We have designed and prepared 6′′‐[ 18 F]fluoromaltotriose (8 ) as a PET tracer for imaging bacterial infection. A successful synthesis of8 has been accomplished with 8 ± 1.2% radiochemical yield ( N  = 6) (decay corrected).